Adoção de novos modelos de precificação em telecomunicações: estudo exploratório sobre os direcionadores e barreiras no mercado brasileiro - Gildin, Andre (2014)
The Brazilian telecommunication and information technology market (ICT) has a significant importance for the Brazilian development as a whole, given the evolution of the mobile market that has grown 600% in the last 10 years. The telecommunication (telecom) industry which represents 4,7% of the GDP in Brazil (Telebrasil, 2013), has taken on a new momentum since the introduction of the General Law of Telecommunication (LGT) in 1997 and later with the privatization of the sector. The evolution of new technologies and new network architectures has also driven this rapid transformation of the industry value chain, and, moreover, with the surge of the internet and later the applications (APPS) market, the entire telecommunications chain has become more complex, enabling the development of new players, new services, and business and pricing models (SCHAPIRO & VARIAN, 2003). This project aims at analyzing the drivers and barriers in the adoption of new service pricing models in the Brazilian telecommunication market, given this new dynamics. This study was done through a qualitative-exploratory and interpretative approach. It is based on the Multilevel framework (POZZEBON & DINIZ, 2012) derived from the analysis of interactions between relevant social groups. Based on this methodology, it was possible to analyze the criteria, drivers and barriers in the adoption of new pricing models, where the user demands, high competition and the need to increase the return over the investments are highlighted as the main drivers. The network quality, the lack of systems, operator´s financial situation, the complexity of the regulatory environment and the distinct social groups within the operator have been pointed as the main barriers throughout the process. In this context, the emerging pricing models covers the converged services, limited period offers, sponsorships/free services in conjunction with exploration of new business areas. This study provides a practical and academic contribution as it can be used for a better comprehension of the Brazilian telecommunication market dynamic as well as it can be applied towards the areas of strategic and tactical marketing within operators, as well as policy formulation and sector regulation.